2021
DOI: 10.2138/gselements.17.5.321
|View full text |Cite
|
Sign up to set email alerts
|

Carbonatitic Melts and Their Role in Diamond Formation in the Deep Earth

Abstract: Carbonatitic high-density fluids and carbonate mineral inclusions in lithospheric and sub-lithospheric diamonds reveal comparable compositions to crustal carbonatites and, thus, support the presence of carbon-atitic melts to depths of at least the mantle transition zone (~410–660 km depth). Diamonds and high pressure–high temperature (HP–HT) experiments confirm the stability of lower mantle carbonates. Experiments also show that carbonate melts have extremely low viscosity in the upper mantle. Hence, carbonati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Such integrated studies are providing new insights into the nature and origin of the diverse spectrum of carbonatites, the role of carbonate in the mantle, and the sources of carbon in carbonatites. Similarly, Ca isotopic compositions of carbonatites (Amsellem et al 2020) and chemical and isotopic compositions of inclusions and their diamond host (e.g., using O isotopes) (Timmerman et al 2021 this issue) are providing increasing evidence of recycling of crustal carbonates during subduction into the deep, convecting mantle as a major source of carbon in carbonatite rocks.…”
Section: Discussionmentioning
confidence: 99%
“…Such integrated studies are providing new insights into the nature and origin of the diverse spectrum of carbonatites, the role of carbonate in the mantle, and the sources of carbon in carbonatites. Similarly, Ca isotopic compositions of carbonatites (Amsellem et al 2020) and chemical and isotopic compositions of inclusions and their diamond host (e.g., using O isotopes) (Timmerman et al 2021 this issue) are providing increasing evidence of recycling of crustal carbonates during subduction into the deep, convecting mantle as a major source of carbon in carbonatite rocks.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental works have shown that at P-T parameters of the lithospheric mantle, carbonate/alkaline-carbonate melts can be in equilibrium or in partial equilibrium with various mantle mineral assemblages (e.g., [47][48][49][50][51][52][53][54][55][56]). It is currently accepted that these melts can be generated by low degrees of partial melting of mantle rocks (e.g., [24,[57][58][59][60][61][62][63]).…”
Section: Introductionmentioning
confidence: 99%
“…Carbonate melts display unique physical properties, such as the lowest viscosities among known terrestrial melts, high mobility and wettability (e.g., [63]). Hence, carbonatitic melts may be highly effective metasomatic agents in the lithospheric mantle, as their low viscosity and high mobility permit percolation along grain boundaries of silicates over a large distance (e.g., [64]).…”
Section: Introductionmentioning
confidence: 99%